STRATEGI IMPLEMENTASI NILAI-NILAI MODERASI BERAGAMA DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI SMP DEK PADANG TAHUN AJARAN 2024 / 2025 - Mohamad Tabri; Remiswal Remiswal; Efendi Efendi (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2026)
This research is motivated by the importance of strengthening the values ​​of religious moderation in facing societal diversity and the potential for radicalism among students, where schools have a strategic role through Islamic religious education learning. This study aims to describe the values ​​of religious moderation, school policies, and their implementation strategies in Islamic religious education learning at SMP DEK Padang in the 2024/2025 academic year. The approach used is a qualitative descriptive case study, with data collection techniques through observation, interviews, and documentation of the principal, Islamic religious education teachers, and students. Data analysis was carried out inductively including data reduction, data presentation, and drawing conclusions. The results show that the implemented values ​​of religious moderation include tolerance, balance (tawazun), justice (i'tidal), anti-violence, and respect for differences in beliefs that are internalized through social interactions within the school community. School policies fully support this implementation through the principle of non-discrimination and equal educational services. The implementation strategy is integrated through intracurricular activities (teaching materials and dialogic methods), extracurricular activities, and school culture through teacher role models and social practices. This strategy has proven effective in building inclusive religious understanding, preventing extremist attitudes, and developing tolerant and national-minded students.